A lithium ion battery positive electrode slurry dispersant and preparation method thereof
By using a specific composition dispersant in the positive electrode slurry of lithium iron phosphate slurry, the problem of increasing the solid content and reducing viscosity of lithium iron phosphate slurry is solved, and the solid content and more stable fluidity are achieved, and the overall quality of lithium ion batteries is improved.
Patent Information
- Application Number
- CN202211718575.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-29
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2042-12-29
AI Technical Summary
The prior art is difficult to increase the solid content of lithium iron phosphate positive electrode slurry while maintaining or reducing the viscosity to ensure fluidity and stability.
The lithium-ion battery positive electrode slurry dispersant prepared by radical polymerization reaction of cationic monomer, polyether macromonomer and double bonded cyclic compounds is used to improve the dispersant effect and reduce the viscosity of lithium iron phosphate slurry by adjusting the component ratio and polymerization reaction conditions.
The solid content of lithium iron phosphate slurry was successfully increased to 55%-60% by weight, the viscosity of the material was reduced to within 10,000 mPa·s, and the viscosity was kept stable. After 72 hours, the viscosity changed within 20%, which significantly improved the quality of the lithium-ion battery.
Smart Images

Figure BDA0004028071400000021 
Figure BDA0004028071400000022 
Figure BDA0004028071400000081
Abstract
Description
Technical Field
[0001] The invention relates to the field of lithium battery dispersants, and in particular to a lithium ion battery positive electrode slurry dispersant and a preparation method thereof. Background Art
[0002] Lithium-ion battery is a rechargeable battery with broad application prospects. It has high energy density, long life, small size, no maintenance, and is environmentally friendly. It is favored by various industries and has moved from the fields of mobile phones and laptops to electric bicycles, electric vehicles, energy storage and various portable devices. It is an ideal mobile power source.
[0003] Lithium-ion batteries are mainly composed of positive electrodes, negative electrodes, separators and electrolytes. The positive and negative electrodes are made by mixing active materials, conductive agents and adhesives into slurry and then coating them on the current collector. The negative electrode active material is usually a carbon material. The positive electrode active material is usually a lithium-containing compound. Currently, the positive electrode active materials that have been widely used in the market are mainly lithium iron phosphate, lithium manganese oxide, ternary materials lithium nickel cobalt manganese oxide and lithium nickel cobalt aluminum oxide. Among them, lithium iron phosphate as a positive electrode has the characteristics of low cost, high safety and long cycle life, and is increasingly valued and widely used.
[0004] The solid content of the lithium iron phosphate positive electrode slurry used in the positive electrode preparation process is usually 50wt%-55wt%. When the solid content of the slurry is further increased, the viscosity of the slurry will increase significantly, the viscosity changes greatly during storage, the fluidity of the slurry decreases, the construction difficulty increases, and the electrical performance decreases. Therefore, a dispersant is needed to change the viscosity and fluidity of the slurry. However, there is currently little research on dispersants for positive electrode active materials, and there are relatively few commercial products that can be used. Therefore, how to increase the solid content of lithium iron phosphate positive electrode slurry, reduce the viscosity of the slurry and maintain the fluidity and stability of the slurry is currently a major problem, so there is still room for improvement. Summary of the invention
[0005] In order to better improve the dispersibility of lithium iron phosphate positive electrode slurry, the present application provides a lithium ion battery positive electrode slurry dispersant and a preparation method thereof.
[0006] In a first aspect, the present application provides a lithium-ion battery positive electrode slurry dispersant, which adopts the following technical solution: a lithium-ion battery positive electrode slurry dispersant, which is prepared by free radical polymerization reaction of the following components in mass percentage:
[0007] Cationic monomer 5-30%;
[0008] Polyether macromonomer 10-50%;
[0009] Cyclic compounds with double bonds 20-85%;
[0010] The structural formula of the cationic monomer is as follows:
[0011]
[0012] The R1 is -H or -CH3;
[0013] Said R2 is -CH2-CH2-;
[0014] R3 is -CH3 or -CH2-CH3;
[0015] The R4 is -CH3 or -CH2-CH3;
[0016] Said R5 is -CH3 or -CH2-CH3;
[0017] The X - CH3SO4 - or Cl - ;
[0018] The structural formula of the polyether macromonomer is as follows:
[0019]
[0020] Said R6 is H or -CH3;
[0021] Said Y is a C1-C4 alkylene group or a carbonyl group;
[0022] Said R7 is H or -CH3;
[0023] Said n is 1-50;
[0024] The m is 1-50.
[0025] By adopting the above technical solution, the prepared dispersant can increase the solid content of lithium iron phosphate slurry to 55wt%-60wt%, reduce the viscosity of the material to within 10000mPa·s, and keep the viscosity of the material stable. After being placed for 72 hours, the viscosity change is within 20%, so that the quality of the prepared lithium ion battery is better.
[0026] Preferably, the cationic monomer can be one or more of (meth)acryloyloxyethyltrimethylammonium chloride, (meth)acryloyloxyethyltriethylammonium chloride, (meth)acryloyloxyethyldimethylethylammonium chloride, (meth)acryloyloxyethyldiethylmethylammonium chloride, (meth)acryloyloxyethyltrimethylammonium methylsulfate, (meth)acryloyloxyethyltriethylammonium ethylsulfate, methacryloyloxyethyldimethylethylammonium ethylsulfate, and methacryloyloxyethyldiethylmethylammonium methylsulfate.
[0027] Preferably, the polyether macromonomer can be one or more of polyethylene glycol (2000) methacrylate, methallyl polyoxyethylene ether (2000), polypropylene glycol (500) methacrylate, allyl polyoxyethylene ether (2400), polyethylene glycol (550) methacrylate, polyethylene glycol (200) acrylate, polyethylene glycol (200) propylene glycol (300) methacrylate. The numbers in brackets represent the molecular weight of the corresponding polyethylene glycol or polypropylene glycol part, such as polyethylene glycol (2000) methacrylate refers to the methacrylate of polyethylene glycol with a molecular weight of 2000.
[0028] Preferably, the cyclic compound with a double bond may be one or more of styrene, methylstyrene, vinylpyridine, and N-vinylpyrrolidone.
[0029] Preferably, the weight average molecular weight of the polyether macromonomer is ≤5000Da.
[0030] By adopting the above technical solution, the dispersing effect of the dispersant is improved, the viscosity of the lithium iron phosphate slurry is better and continuously reduced, and the viscosity change is better reduced.
[0031] Preferably, the weight average molecular weight of the lithium ion battery positive electrode slurry dispersant is 3000-100000Da.
[0032] By adopting the above technical solution, the prepared dispersant has a better dispersing effect on lithium iron phosphate slurry. After the viscosity decreases, the change in viscosity is small, and a high fluidity is maintained in a long-lasting and stable manner.
[0033] In a second aspect, the present application provides a method for preparing a lithium-ion battery positive electrode slurry dispersant, using the following technical solution:
[0034] A method for preparing a lithium ion battery positive electrode slurry dispersant comprises the following steps:
[0035] Step 1), mixing a solvent, a cationic monomer, a polyether macromonomer, and a cyclic compound with a double bond to obtain a mixed solution;
[0036] Step 2), heating the mixed solution to a reaction temperature, adding an initiator, and maintaining the reaction temperature to react to obtain a lithium-ion battery positive electrode slurry dispersant.
[0037] By adopting the above technical solution, the quality of the prepared dispersant is better, the effect of dispersing lithium iron phosphate slurry is better, the viscosity of lithium iron phosphate slurry with high solid content is effectively reduced, and the fluidity of lithium iron phosphate slurry is improved.
[0038] Preferably, the solvent is N-methylpyrrolidone.
[0039] By adopting the above technical solution and using N-methylpyrrolidone as the solvent, there is no need to remove the solvent and then replace it with N-methylpyrrolidone, so the process is simple and it is easier to prepare the slurry.
[0040] Preferably, the initiator is azobisisobutyronitrile.
[0041] By adopting the above technical scheme and specifically selecting azobisisobutyronitrile as the initiator, the reaction efficiency is higher, the reaction effect is higher, the quality of the prepared dispersant is better, the time required for the process is shortened, and the economic value is higher.
[0042] Preferably, in step 2), the reaction temperature is 50-90°C.
[0043] By adopting the above technical solution and specifically selecting the reaction temperature, the reaction speed can be made more appropriate, which can not only maintain a high reaction speed, but also effectively reduce the generation of by-products, so that the quality of the prepared dispersant is better.
[0044] Preferably, in step 2), the reaction temperature is maintained for 3-24 hours.
[0045] By adopting the above technical solution, the reaction time is controlled, the reaction is sufficient, the energy consumption is controlled, and higher economic value is achieved.
[0046] In summary, this application has the following beneficial effects:
[0047] 1. Since the dispersant prepared in the present application can increase the solid content of lithium iron phosphate slurry to 58wt%-60wt%, the viscosity of the material is reduced to within 10000mPa·s, and the viscosity of the material is kept stable. After being placed for 72 hours, the viscosity change is within 20%, so that the quality of the prepared lithium ion battery is better.
[0048] 2. In the present application, the weight average molecular weight of the lithium-ion battery positive electrode slurry dispersant is preferably 3000-100000Da, so that the prepared dispersant has a better dispersing effect on the lithium iron phosphate slurry, and after the viscosity decreases, the viscosity changes less, and a high fluidity is maintained stably and permanently. DETAILED DESCRIPTION
[0049] The present application is further described in detail below in conjunction with embodiments.
[0050] Example 1
[0051] A lithium-ion battery positive electrode slurry dispersant is prepared by polymerization of (meth)acryloyloxyethyl trimethylammonium chloride, polyethylene glycol 5000 methacrylate and N-vinyl pyrrolidone.
[0052] The preparation method of the lithium ion battery positive electrode slurry dispersant comprises the following steps:
[0053] Step 1), 700 g of ethanol, 35 g of (meth)acryloyloxyethyltrimethylammonium chloride, 70 g of polyethylene glycol 5000 methacrylate and 595 g of N-vinyl pyrrolidone were added to a 2L five-necked round-bottom flask equipped with a nitrogen device, a stirring device, a reflux condenser and a thermometer, the speed was 60 r / min, and the mixture was stirred for 5 min to obtain a mixed solution;
[0054] Step 2), nitrogen was passed and the temperature was raised to 70°C, then 7g of azobisisobutyronitrile was added, the temperature was kept at 70°C, the speed was 60r / min and continuous stirring was performed, and the reaction was stopped after 6 hours, the obtained polymer solution was heated to remove ethanol, and then 700g of N-methylpyrrolidone was added, the speed was 60r / min, and the lithium ion battery positive electrode slurry dispersant was obtained after stirring and dissolving.
[0055] Example 2
[0056] A lithium-ion battery positive electrode slurry dispersant is prepared by polymerization of (meth)acryloyloxyethyl triethylammonium chloride, polyethylene glycol (2000) methacrylate and N-vinyl pyrrolidone.
[0057] The preparation method of the lithium ion battery positive electrode slurry dispersant comprises the following steps:
[0058] Step 1), 700 g of ethanol, 140 g of (meth)acryloyloxyethyl triethylammonium chloride, 210 g of polyethylene glycol (2000) methacrylate and 350 g of N-vinyl pyrrolidone were added to a 2L five-necked round-bottom flask equipped with a nitrogen device, a stirring device, a reflux condenser and a thermometer, the mixture was stirred at a speed of 60 r / min for 5 min to obtain a mixed solution;
[0059] Step 2), nitrogen was passed and the temperature was raised to 50°C, then 7g of azobisisobutyronitrile was added, the temperature was kept at 50°C, the speed was 60r / min and continuous stirring was performed, and the reaction was stopped after 24 hours, the obtained polymer solution was heated to remove ethanol, and then 700g of N-methylpyrrolidone was added, the speed was 60r / min, and the lithium ion battery positive electrode slurry dispersant was obtained after stirring and dissolving.
[0060] Example 3
[0061] A lithium-ion battery positive electrode slurry dispersant is prepared by polymerization of (meth)acryloyloxyethyl dimethylethyl ammonium chloride, methyl allyl oxyethylene ether 2000 and vinyl pyridine.
[0062] The preparation method of the lithium ion battery positive electrode slurry dispersant comprises the following steps:
[0063] Step 1), 700 g of ethanol, 210 g of (methyl)acryloyloxyethyl dimethylethylammonium chloride, 210 g of methyl allyl oxyethylene ether 2000 and 280 g of vinyl pyridine were added to a 2L five-necked round-bottom flask equipped with a nitrogen device, a stirring device, a reflux condenser and a thermometer, the speed was 60 r / min, and the mixture was stirred for 5 min to obtain a mixed solution;
[0064] Step 2), pass nitrogen and heat to 90 ° C, then add 7g of azobisisobutyronitrile, keep warm at 90 ° C, keep stirring at 60r / min, stop the reaction after 3 hours, heat the obtained polymer solution to remove ethanol, then add 700g of N-methylpyrrolidone, rotate at 60r / min, stir and dissolve to obtain a lithium ion battery positive electrode slurry dispersant.
[0065] Example 4
[0066] A lithium-ion battery positive electrode slurry dispersant is prepared by polymerization of (meth)acryloyloxyethyl diethyl methyl ammonium chloride, polypropylene glycol (500) methacrylate and methyl styrene.
[0067] The preparation method of the lithium ion battery positive electrode slurry dispersant comprises the following steps:
[0068] Step 1), 700 g of N-methylpyrrolidone, 210 g of (methyl)acryloyloxyethyl diethyl methylammonium chloride, 210 g of polypropylene glycol (500) methacrylate and 280 g of methylstyrene were added to a 2L five-necked round-bottom flask equipped with a nitrogen device, a stirring device, a reflux condenser and a thermometer, the speed was 60 r / min, and the mixture was stirred for 5 min to obtain a mixed solution;
[0069] Step 2), nitrogen was passed through and the temperature was raised to 70°C, then 7g of azobisisobutyronitrile was added, the temperature was kept at 70°C, the speed was 60r / min and the stirring was continued, and the reaction was stopped after 6 hours to obtain a lithium-ion battery positive electrode slurry dispersant.
[0070] Example 5
[0071] A lithium-ion battery positive electrode slurry dispersant is prepared by polymerization of (meth)acryloyloxyethyl trimethylammonium methylsulfate, allyl polyoxyethylene ether (2400) and N-vinyl pyrrolidone.
[0072] The preparation method of the lithium ion battery positive electrode slurry dispersant comprises the following steps:
[0073] Step 1), add 700g of ethanol, 70g of ((meth)acryloyloxyethyl trimethylammonium methylsulfate, 350g of allyl polyoxyethylene ether (2400) and 280g of N-vinyl pyrrolidone into a 2L five-necked round-bottom flask equipped with a nitrogen device, a stirring device, a reflux condenser and a thermometer, rotate at 60r / min, stir for 5min, and obtain a mixed solution;
[0074] Step 2), nitrogen was passed and the temperature was raised to 70°C, then 7g of azobisisobutyronitrile was added, the temperature was kept at 70°C, the speed was 60r / min and continuous stirring was performed, and the reaction was stopped after 6 hours, the obtained polymer solution was heated to remove ethanol, and then 700g of N-methylpyrrolidone was added, the speed was 60r / min, and the lithium ion battery positive electrode slurry dispersant was obtained after stirring and dissolving.
[0075] Example 6
[0076] A lithium-ion battery positive electrode slurry dispersant is prepared by polymerization of acryloyloxyethyl triethyl ammonium ethyl sulfate, polyethylene glycol (550) methacrylate and styrene.
[0077] The preparation method of the lithium ion battery positive electrode slurry dispersant comprises the following steps:
[0078] Step 1), 700 g of ethanol, 105 g of acryloyloxyethyl triethylammonium sulfate, 350 g of polyethylene glycol (550) methacrylate and 245 g of styrene were added to a 2L five-necked round-bottom flask equipped with a nitrogen device, a stirring device, a reflux condenser and a thermometer, and the mixture was stirred at a speed of 60 r / min for 5 min to obtain a mixed solution;
[0079] Step 2), nitrogen was passed and the temperature was raised to 70°C, then 7g of azobisisobutyronitrile was added, the temperature was kept at 70°C, the speed was 60r / min and continuous stirring was performed, and the reaction was stopped after 6 hours, the obtained polymer solution was heated to remove ethanol, and then 700g of N-methylpyrrolidone was added, the speed was 60r / min, and the lithium ion battery positive electrode slurry dispersant was obtained after stirring and dissolving.
[0080] Example 7
[0081] A lithium-ion battery positive electrode slurry dispersant is prepared by polymerization of (meth)acryloyloxyethyl dimethyl ethyl ammonium sulfate, polyethylene glycol (200) acrylate and N-vinyl pyrrolidone.
[0082] The preparation method of the lithium ion battery positive electrode slurry dispersant comprises the following steps:
[0083] Step 1), 700 g of ethanol, 70 g of (meth)acryloyloxyethyl dimethyl ethyl ammonium sulfate, 350 g of polyethylene glycol (200) acrylate and 280 g of N-vinyl pyrrolidone were added to a 2L five-necked round-bottom flask equipped with a nitrogen device, a stirring device, a reflux condenser and a thermometer, and the mixture was stirred at a speed of 60 r / min for 5 min to obtain a mixed solution;
[0084] Step 2), nitrogen was passed and the temperature was raised to 70°C, then 7g of azobisisobutyronitrile was added, the temperature was kept at 70°C, the speed was 60r / min and continuous stirring was performed, and the reaction was stopped after 6 hours, the obtained polymer solution was heated to remove ethanol, and then 700g of N-methylpyrrolidone was added, the speed was 60r / min, and the lithium ion battery positive electrode slurry dispersant was obtained after stirring and dissolving.
[0085] Example 8
[0086] A lithium-ion battery positive electrode slurry dispersant is prepared by polymerization of (meth)acryloyloxyethyl diethyl methyl ammonium methyl sulfate, polyethylene glycol (200) propylene glycol (300) methacrylate and vinyl pyridine.
[0087] The preparation method of the lithium ion battery positive electrode slurry dispersant comprises the following steps:
[0088] Step 1), 700 g of ethanol, 105 g of ((meth)acryloyloxyethyl diethyl methyl ammonium sulfate, 280 g of polyethylene glycol (200) propylene glycol (300) methacrylate and 315 g of vinyl pyridine were added to a 2L five-necked round-bottom flask equipped with a nitrogen device, a stirring device, a reflux condenser and a thermometer, the speed was 60 r / min, and the mixture was stirred for 5 min to obtain a mixed solution;
[0089] Step 2), nitrogen was passed and the temperature was raised to 70°C, then 7g of azobisisobutyronitrile was added, the temperature was kept at 70°C, the speed was 60r / min and continuous stirring was performed, and the reaction was stopped after 6 hours, the obtained polymer solution was heated to remove ethanol, and then 700g of N-methylpyrrolidone was added, the speed was 60r / min, and the lithium ion battery positive electrode slurry dispersant was obtained after stirring and dissolving.
[0090] Comparative Example 1
[0091] The dispersant for the positive electrode slurry of lithium-ion batteries is N-polypropylene pyrrolidone.
[0092] Comparative Example 2
[0093] The dispersant of the positive electrode slurry of lithium-ion batteries is polyethylene glycol (550) methacrylate.
[0094] Comparative Example 3
[0095] The dispersant for the positive electrode slurry of lithium-ion batteries is (meth)acrylate trimethylammonium chloride.
[0096] Comparative Example 4
[0097] A lithium-ion battery positive electrode slurry dispersant is prepared by polymerization of (meth)acryloyloxyethyltrimethylammonium methylsulfate and N-vinyl pyrrolidone.
[0098] The preparation method of the lithium ion battery positive electrode slurry dispersant comprises the following steps:
[0099] Step 1), add 700g of ethanol, 140g of (methyl)acryloyloxyethyltrimethylammonium methylsulfate and 560g of N-vinylpyrrolidone into a 2L five-necked round-bottom flask equipped with a nitrogen device, a stirring device, a reflux condenser and a thermometer, rotate at 60r / min, stir for 5min, and obtain a mixed solution;
[0100] Step 2), nitrogen was passed and the temperature was raised to 70°C, then 7g of azobisisobutyronitrile was added, the temperature was kept at 70°C, the speed was 60r / min and continuous stirring was performed, and the reaction was stopped after 6 hours, the obtained polymer solution was heated to remove ethanol, and then 700g of N-methylpyrrolidone was added, the speed was 60r / min, and the lithium ion battery positive electrode slurry dispersant was obtained after stirring and dissolving.
[0101] Comparative Example 5
[0102] A lithium-ion battery positive electrode slurry dispersant is prepared by polymerization of acryloyloxyethyl triethyl ammonium ethyl sulfate and polyethylene glycol (200) propylene glycol (300) methacrylate.
[0103] The preparation method of the lithium ion battery positive electrode slurry dispersant comprises the following steps:
[0104] Step 1), 700 g of ethanol, 210 g of (acryloyloxyethyl triethylammonium sulfate and 490 g of polyethylene glycol (200) propylene glycol (300) methacrylate were added to a 2L five-necked round-bottom flask equipped with a nitrogen device, a stirring device, a reflux condenser and a thermometer, the speed was 60 r / min, and the mixture was stirred for 5 min to obtain a mixed solution;
[0105] Step 2), nitrogen was passed and the temperature was raised to 70°C, then 7g of azobisisobutyronitrile was added, the temperature was kept at 70°C, the speed was 60r / min and continuous stirring was performed, and the reaction was stopped after 6 hours, the obtained polymer solution was heated to remove ethanol, and then 700g of N-methylpyrrolidone was added, the speed was 60r / min, and the lithium ion battery positive electrode slurry dispersant was obtained after stirring and dissolving.
[0106] Comparative Example 6
[0107] A lithium-ion battery positive electrode slurry dispersant is prepared by polymerization of polyethylene glycol 5000 methacrylate and N-vinyl pyrrolidone.
[0108] The preparation method of the lithium ion battery positive electrode slurry dispersant comprises the following steps:
[0109] Step 1), add 700g of ethanol, 350g of polyethylene glycol 5000 methacrylate and 350g of N-vinyl pyrrolidone into a 2L five-necked round-bottom flask equipped with a nitrogen device, a stirring device, a reflux condenser and a thermometer, rotate at 60r / min, stir for 5min, and obtain a mixed solution;
[0110] Step 2), nitrogen was passed and the temperature was raised to 70°C, then 7g of azobisisobutyronitrile was added, the temperature was kept at 70°C, the speed was 60r / min and continuous stirring was performed, and the reaction was stopped after 6 hours, the obtained polymer solution was heated to remove ethanol, and then 700g of N-methylpyrrolidone was added, the speed was 60r / min, and the lithium ion battery positive electrode slurry dispersant was obtained after stirring and dissolving.
[0111] Experiment 1
[0112] A lithium ion battery positive electrode slurry was prepared by using the lithium ion battery positive electrode slurry dispersant of each embodiment and comparative example, and the viscosity and solid content of the lithium ion battery positive electrode slurry were tested.
[0113] 1. Preparation of positive electrode slurry for lithium-ion batteries:
[0114] The lithium-ion battery positive electrode slurry has a solid content of 58-60wt%, and the solid components include 94wt% of lithium iron phosphate, 0.4wt% of a dispersant, 2.6wt% of conductive carbon black, and 3wt% of a binder PVDF.
[0115] The preparation method of lithium-ion battery positive electrode slurry is as follows:
[0116] First, 18 g of binder PVDF was dissolved in 400 g of N-methylpyrrolidone solvent to prepare a solution, and 564 g of lithium iron phosphate, 15.6 g of conductive carbon black and 2.4 g of dispersant were added in sequence at a speed of 120 r / min and stirred for 30 min to allow the powder material to be fully and evenly mixed in the solvent to obtain lithium iron phosphate positive electrode slurry.
[0117] The dispersants are the lithium ion battery positive electrode slurry dispersants prepared in the embodiments and comparative examples.
[0118] 2. Viscosity test:
[0119] The sample was kept in a 25°C thermostat for 2 hours, and the viscosity of the material was tested using a NDJ5S digital rotational viscometer. The sample was then kept in a 25°C thermostat for 72 hours, and the viscosity of the material was tested again using a NDJ5S digital rotational viscometer.
[0120] 3. Use a lithium battery rubber solid content tester to test the solid content of the sample.
[0121] Experiment 2
[0122] GPC gel permeation chromatography was used to detect the molecular weight of the lithium ion battery positive electrode slurry dispersant prepared in each embodiment and comparative example.
[0123] The specific test data of Experiments 1 and 2 are shown in Table 1.
[0124] Table 1
[0125]
[0126]
[0127] According to the data in Table 1, the lithium-ion battery positive electrode slurry dispersant prepared in each embodiment has an excellent effect. When the solid content of the positive electrode slurry is as high as 58-60wt%, the viscosity of the positive electrode slurry can be reduced to less than 10000mPa.s, and the viscosity changes less after 72h, which is controlled within 20%. The viscosity is stable and the system stability is high.
[0128] However, the viscosity reduction effect of each comparative example on the positive electrode slurry with a solid content of up to 58-60wt% is weak, the viscosity changes greatly after 72h, and the stability is poor.
[0129] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A lithium ion battery positive electrode slurry dispersant, characterized in that: Prepared by free radical polymerization of the following components in percentage by mass: Cationic monomer 5-30%; Polyether macromonomer 10-50%; Cyclic compounds with double bonds 20-85%; The structural formula of the cationic monomer is as follows: The R1 is -H or -CH3; Said R2 is -CH2-CH2-; R3 is -CH3 or -CH2-CH3; The R4 is -CH3 or -CH2-CH3; Said R5 is -CH3 or -CH2-CH3; The X - CH3SO4 - or Cl - ; The structural formula of the polyether macromonomer is as follows: Said R6 is H or -CH3; Said Y is a C1-C4 alkylene group or a carbonyl group; Said R7 is H or -CH3; Said n is 1-50; The m is 1-50; The cyclic compound with a double bond may be one or more of styrene, methylstyrene, vinylpyridine, and N-vinylpyrrolidone.
2. A lithium ion battery positive electrode slurry dispersant according to claim 1, characterized in that: The weight average molecular weight of the polyether macromonomer is ≤5000Da.
3. A lithium ion battery positive electrode slurry dispersant according to claim 2, characterized in that: The weight average molecular weight of the lithium ion battery positive electrode slurry dispersant is 3000-100000Da.
4. A method for preparing a lithium-ion battery positive electrode slurry dispersant according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1), mixing a solvent, a cationic monomer, a polyether macromonomer, and a cyclic compound with a double bond to obtain a mixed solution; Step 2), heating the mixed solution to a reaction temperature, adding an initiator, and maintaining the reaction temperature to react to obtain a lithium-ion battery positive electrode slurry dispersant.
5. The method for preparing a lithium ion battery positive electrode slurry dispersant according to claim 4, characterized in that: The solvent is N-methylpyrrolidone.
6. The method for preparing a lithium ion battery positive electrode slurry dispersant according to claim 5, characterized in that: The initiator is azobisisobutyronitrile.
7. The method for preparing a lithium ion battery positive electrode slurry dispersant according to claim 4, characterized in that: In the step 2), the reaction temperature is 50-90°C.
8. The method for preparing a lithium ion battery positive electrode slurry dispersant according to claim 7, characterized in that: In the step 2), the reaction temperature is maintained for 3-24 hours.
Citation Information
Patent Citations
Conductive paste and mixture paste for lithium ion battery positive electrode
CN107528067A
Dispersing agent for lithium ion battery, preparation method of dispersing agent, positive electrode slurry, positive electrode plate and lithium ion battery
CN114573751A